BSAVA manual of canine and feline endoscopy and endosurgery - Lhermette, Philip; Sobel, David, 1965-; Robertson, Elise (British Small Animal Veterinary Association, 2020)
The BSAVA Manual of Canine and Feline Endoscopy and Endosurgery provides a comprehensive and practical guide for practitioners who wish to practice minimally invasive techniques. Routine procedures are described in detail and more advanced techniques suitable for advanced practitioners are also included. All the chapters have been thoroughly revised and updated, and chapters on oesophagoscopy, interventional endoscopy and future developments are new to this edition. Detailed information on minimally invasive techniques in cats is included throughout, and the chapter on laparoscopy has been significantly expanded and covers techniques ranging from liver biopsy and ovariectomy to cholecystectomy and adrenalectomy. Exclusive video content New to this edition are a series of videos that accompany the chapters. These videos are available from the BSAVA Library and information on how to access this is provided within the book.